Injury history is associated with sport specialization level in high school volleyball athletes - Biese, K. M.; McGuine, T. A.; Hernandez, M. I.; Schaefer, D. A.; Kliethermes, S.; Brooks, M. A.; Watson, A.; Lang, P.; Bell, D. R. (Journal of Athletic Training, 2019)
"Context: Sport specialization has been associated with increased risk of musculoskeletal lower extremity injuries in adolescent athletes. However, many studies neglected to control for the sport a participant specialized in when evaluating risk of injury. More research is needed to fully understand the risk of specialization as it pertains to a given sport. Volleyball, for example, is one of the most popular high school sports in the United States and has a history of club sport participation and specialization. Additionally, the sport of volleyball lends itself to repetitive actions, such as jumping and hitting, which may elevate injury risk. Therefore, the purpose of this study was to determine if sport specialization level is associated with musculoskeletal injury history in high school volleyball athletes. Methods: This study was a cross-sectional survey. Participants (female, interscholastic athletes, grades 9-12) were recruited from a diverse sample of 79 Wisconsin high schools during the 2018 volleyball season. A total of 2,077 participants (Age=15.1+1.1 yrs.) enrolled in the study. Participants completed a questionnaire consisting of 1) demographic information, 2) sport specialization scale, 3) sport participation information, and 4) sport related injury in the previous 12 months. Sport specialization status was determined using a widely utilized 3 item specialization scale (total score: 0-1=Low, 2=Moderate, 3=High). Multivariable logistic regression analyses were used to investigate the association between sport specialization with history of lower extremity injury while adjusting for grade level. Additionally, a one-way ANOVA with LSD post-hoc analysis was used to evaluate the difference between sport specialization categories and the age when volleyball became the participant`s primary sport. Results: Twenty-two percent of the sample was classifi ed as highly specialized (Low: 54.9%, Moderate: 22.7%, High: 22.5%), while 49.9% participated in club volleyball in the past year in addition to their high school team. Moderate and highly specialized athletes considered volleyball their primary sport at a younger age than their low specialized counterparts (F = 21.4, p<0.001; Low- Moderate = 0.50 yrs, p<0.001, 95% CI: 0.29-0.70; Low-High = 0.64 yrs, p<0.001, 95%CI: 0.43-0.84). The odds of reporting any musculoskeletal injury (OR=1.68 (95%CI: 1.33-2.11)) and a lower extremity injury in the past 12 months (OR=1.73 (95%CI: 1.35-2.21)) were greater among Highly specialized athletes compared to Low specialization athletes. Conclusions: Volleyball players have high participation in club teams, lending themselves to yearround participation and high levels of specialization. Highly specialized volleyball players were approximately 68-75% more likely to have a previous musculoskeletal injury history in the past 12 months compared to low specialization athletes, after adjusting for grade level. Youth athletes, parents, coaches, and clinicians should be aware of the potential risks of intense, yearround participation in organized sports, especially volleyball. Efforts aimed at increasing safe sport awareness and education should be targeted within the volleyball community."